Quality of life in the work: a perception of workers who had returned to formal education - Andrade, Alexandro (2010)
The aim of this article was to analyze the perception of the quality of life at work from workers who had returned to formal high school due to market demands. The main changes related to work and some aspects of their lives were investigated. 6 young professionals and adults from educational field were part of this study, 3 male and 3 female that concluded the High School of the Young and Adults Program of Education in the State of Santa Catarina. This study was based on subjects’ experiences, as well as some classic and contemporary authors’ ideas. The results indicated that the workers quality of life improved meaningfully, on their professional life as well as on their personal life. Their opinion about the Programs they have participated, it was noticed that they considered those Programs of primary importance to provide opportunities, however, the workers pointed the necessity of a more specific pedagogic proposal, suggesting more appropriate contents to work students in their daily life.